Interview in organizations, a psychological perspective for its classification and application - Perea Rivera, José Luis (2008)
The interview is seen as a general theme in the broad spectrum of the professional activity of the sciences and humanities, and the importance being given in the handling or use, method or technique can be as a tool for research scientific, via the communication sciences, law, until the fields of malaise (illness), or welfare (health) where the psychology, and particularly within the psychology of it as an organizational tool, which for This exploratory research, is treated comparably between their ability based on knowledge of rules and structure, and its dynamics based on the functional purpose of managing the organization to achieve its objectives of growth and development of this analysis results have been systematized that allow to pose a model for a classification and application of the interview in the field of organizations. The structuring of the model sets criteria systematized as an alternative propositions under a systems approach, which helps in coping with the various demands of the twenty-first century, which will be attended by organizations of the era of globalization.